UPAYA PENINGKATAN PERFORMANSI SISWA MELALUI METODE TUGAS PROYEK PEMBUATAN DONGKRAK HIDROLIS SEDERHANA MATERI PENERAPAN KONSEP TEKANAN ZAT PADA SISWA KELAS VIII-F TP. 2022/2023 - Lailatul Chusniah (Program Pascasarjana Universitas Islam Darul `Ulum Lamongan, 2023)
Substance Pressure is a difficult material for most of the 8F students. They complained about how to understand and apply the concept in daily life. They liked social science than natural science. They prefered to memorize to calculate. Some students seldom submitted their assignments. Even at the end of odd semester there were three students who did not submit their assignments. Based on the problem, we tried to do a research entitled Upaya Peningkatan Performansi Siswa melalui Metode Tugas Proyek Pembuatan Dongkrak Hidrolis Sederhana pada Materi Penerapan Konsep Tekanan Zat di Kelas VIII-F TP. 2022/2023 (The effort of increasing students performances using the method of project assignment on the making of simple hydraulic jack on the substance pressure concept material at 8F class of MTs N 1 Lamongan 2022/2023 academic year. The class action research was conducted at 8F students of MTs N 1 Lamongan on the 20th February until 11Th March 2023. The subject of this research was the students of 8F class at MTs N 1 Lamongan 2022/2023 academic year. The total number of the students at 8F class is 29 students. The collecting data technique in this research was conducted by using pre test, post test and observation on the teaching learning process. the data of the evaluation test and the observation done by the observer (collaborator) indicated that there was a significant increase on the result of the test and the teaching learning activity done by the researcher. The research used teaching learning based project. In the teaching learning based project, the students were expected to be able to decide the schedules and create products. The class action research was conducted in two cycles. Based on the result of the test in cycle 1 and 2, it indicated that there was significant increase on the score as much as 10.2 each student.